The Effect of Workload and Performance Evaluation on Employee Performance at PT Sinergi Visi Utama - Pramesty Sulistyoning Putri; Fereshti Nurdiana Dihan (PT SOLUSI EDUKASI BERDIKARI, 2024)
High workload is one of the problems affecting employees of PT Sinergi Visi Utama. Employees are expected to complete tasks or responsibilities within a limited time, which negatively affects the physical and mental well-being of employees. The research was conducted using qualitative methods. The high workload at PT Sinergi Visi Utama in the past six months has had a significant impact on employees' physical and mental health, often forcing them to work overtime or take work home. Employees are often forced to work overtime four times a week or take work home. The evaluation process at PT Sinergi Visi Utama involves various aspects such as punctuality, work quality, soft skills, teamwork, and employee adaptability. The conclusion is that the high workload over the past six months has affected employees' physical and mental health. PT Sinergi Visi Utama balances high workload management with a focus on employee development and cooperation with external partners and structured performance evaluation.